Implementasi pajak penghasilan pasal 23 dan 26: Tinjauan literatur dalam konteks perpajakan - Sholahudin, Aris Athoillah; Rahmawati, Zulfa Muasaroh Binti; Ayu, Diyah Isthi; Wijayanti, Uut (Maliki Interdisciplinary Journal, 2024)
This research aims to provide education about the implementation of Income Tax (PPh) Article 26, both regarding what is meant by PPh Article 26, tax objects, tax subjects, and how to calculate PPh Article 26. Given that the government is now implementing a Self-assessment system that requires taxpayers to determine and calculate their own taxes. This research method uses a qualitative research method with a descriptive approach, which is to analyze and describe the data obtained regularly, then given an understanding and explanation so that it can be understood properly by the reader. Income Tax Article 26 (PPh Pasal 26) is a tax imposed on income received by individuals or companies categorized as foreign taxpayers in accordance with applicable provisions and requirements. The general rate for ITA 26 is 20%, but the rate can change if it follows a tax treaty / Double Tax Avoidance Agreement (P3B). After calculating the amount of PPH 26 that must be withheld and paid. The party that pays the income is obliged to submit the required tax reports and documents to the Directorate General of Taxes.